Social Safety Nets in the Global Response to COVID-19 - Gilligan, Daniel O. (2020)
“IFPRI Egypt Webinars” is a special edition of the IFPRI Egypt Seminar Series funded by USAID. This webinar took place under the title of “COVID-19 and social protection: from effective crisis protection to self-reliance”